Co-simulation of the Unreal Engine and MATLAB/Simulink for Automated Grain Offoading. Issue 24 (2022) - Jiang, Chufan; Dhamankar, Shveta; Liu, Ziping; Vinod, Gautham; Shaver, Gregory; Evans, John; Puryk, Corwin; Anderson, Eric; DeLaurentis, Daniel
Abstract: This paper presents a generic simulation platform with two widely employed software, Simulink and Unreal, to simultaneously simulate the perception in virtual 3D scenarios and system dynamics of automated systems. The proposed CoSim framework improves the accuracy and reduces the development time of automation systems for agricultural crop harvesting and transfer. Strategies using either cameras or LiDAR are supported by the framework. To demonstrate the capability of the proposed CoSim tool, this paper simulates an automated offoading process conducted by a combine-tractor system with a closed-loop controller and a LiDAR-based perception system. The simulation results show that CoSim can be used for both system design and system evaluation.